2016
DOI: 10.1016/j.bbrc.2015.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility of transgenic mice expressing human surfactant protein B genetic variants to Pseudomonas aeruginosa induced pneumonia

Abstract: Surfactant protein B (SP-B) is essential for lung function. Previous studies have indicated that a SP-B 1580C/T polymorphism (SNP rs1130866) was associated with lung diseases including pneumonia. The SNP causes an altered N-linked glycosylation modification at Asn129 of proSP-B, e.g. the C allele with this glycosylation site but not in the T allele. This study aimed to generate humanized SP-B transgenic mice carrying either SP-B C or T allele without a mouse SP-B background and then examine functional suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The hSP-D cDNA fragment was cloned into the basic 3.7-hSP-C/SV40 vector and the recombinant construct was confirmed by DNA sequencing. The processes of recombinant DNA were performed based on the standard methods of molecular cloning 58 , 59 . The 5.3-kb DNA fragment was microinjected into fertilized oocytes from WT C57BL/6 mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hSP-D cDNA fragment was cloned into the basic 3.7-hSP-C/SV40 vector and the recombinant construct was confirmed by DNA sequencing. The processes of recombinant DNA were performed based on the standard methods of molecular cloning 58 , 59 . The 5.3-kb DNA fragment was microinjected into fertilized oocytes from WT C57BL/6 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, all experiments in this study were performed through intratracheal instillation of bioluminescent P . aeruginosa Xen5 at a dose of 1 × 10 6 CFU/50 μl/mouse to induce bacterial pneumonia 59 , 60 . Briefly, mice were anesthetized using intraperitoneal ketamine/xylazine (90 mg/kg ketamine, 10 mg/kg xylazine) injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variant polymorphism of the SFTPB gene has been associated with ARDS (26,27). Ge et al (28) demonstrated that in SFTPB humanized mice, the human SFTPB C allele of the 1580C/T polymorphism (single nucleotide polymorphism rs1130866) was more susceptible to bacterial pneumonia than the SFTPB T allele in vivo. Pneumonia is a frequent cause of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were incubated at 37 °C for at least 1 h prior to assessing the surface tension reducing properties using a constrained sessile drop surfactometer (CSD) as previously reported [27]. Briefly, the system involved a pedestal, 3 mm in diameter with a 1 mm pinhole, placed within a chamber incubated at 37 °C.…”
Section: Methodsmentioning
confidence: 99%